Which relationships matter? Communicating college persistence in the rural non-rural student divide - Stefka, Cassidy (Kansas State University, 2018)
College student persistence has long interested scholars and universities alike (Bean, 1983; Goodman, & Pascarella, 2006; Hlinka, 2017; Moschetti & Hudley, 2014; Pascarella & Terenzini, 2005; Tinto; 1993; 2012). While universities have given attention to the academic integration of students (e.g., their GPA and general academic performance), social integration has become increasingly more studied as an integral component to a student’s likelihood to persist (Tinto, 1993; 2012). This study incorporated social capital theory (Coleman, 1988) as a lens to understand how social integration may affect a student’s likelihood to persist. Using survey methodology and a sample of first-year students at large midwestern university (n = 101), the results showed that strong school social capital in the form of relationships with peers and authority figures at college may help a student overcome structural disadvantages embedded within their family and home community social networks. Specific differences in the formation of social capital between nonrural and rural students were also explored with meaningful results. Rural students were more likely to perceive stronger relationships with authority figures at college than nonrural students, and nonrural students were more likely to perceive their home communities as more supportive of higher education than rural students.
Keywords: Social capital; Persistence; Rural; Communication studies